REVIEW ON ELECTROENCEPHALOGRAPHIC FINDINGS IN PATIENTS WITH ALZHEIMER'S DISEASE - Ivan Todorov; Kosta Kostov (Peytchinski Publishing, 2021)
Nowadays, with the constant enhancement of the longevity of the human population, the spreading of dementia is in steady rising. Among the many different sources of progressive cognitive impairment, Alzheimer's disease plays a major role being the most common reason for mental decline in the elderly population. Alzheimer's disease is a neurodegenerative disease of the central nervous system that leads to progressive cognitive impairment and has severe health, social and economic tolls. The lack of effective treatment and the problems of the daily living that the disease creates for the patients and their families raises many important issues in modern times. Due to the effect on the individuals and the need for a permanent caregiver, it is of high importance to have accessible tools for early diagnostic and assessment of the ongoing treatment. Electroencephalography is a noninvasive, easily reproductive diagnostic method with low cost that can be performed in different stages of the diseases of the central nervous system and give input on the current condition. This review presents the current achievements in the field of the usage of electroencephalography and its specific findings in patients with Alzheimer's disease and the qualitative and quantitative changes that appears and are important for early diagnosis, differential diagnostic, prediction of acceleration of the pathological process, distinguishing of co-existing conditions and follow-up of the effect of the administered treatment.